Atlas of transesophageal color Doppler echocardiography and intraoperative imaging - De Simone, Raffaele; Lange, Rüdiger; Hagl, Siegfried (Springer Berlin Heidelberg, 1994)
This manual introduces the extraordinary diagnostic possibilities of Transesophageal Color Doppler Echocardiography and therefore enables readers to recognize and diagnose a wide range of heart diseases. The atlas covers a comprehensive collection of cardiac pathology, selected from routine perioperative examinations. A CD-ROM will also be available, offering more than 160 movies of examinations and covering all important heart diseases such as abnormalities of the valves
Elektronische Reproduktion der Druck-Ausgabe 6. Dezember 2012
Keywords: Atlas; Diagnostik; Intraoperative Phase; Transösophageale Ultraschallkardiographie